Sedimentary evolution and chemostratigraphy of ediacaran dolomite-phssphorite-shale sucessions of the bocaina formacion, Corumbá group -Central Brazil : implications for the neoproterozoic phosphogenic event. - Hippertt, João Pedro Torrezani Martins (2023)
Programa de Pós-Graduação em Evolução Crustal e Recursos Naturais. Departamento de Geologia, Escola de Minas, Universidade Federal de Ouro Preto.